Is Dietary Milk Intake Associated with Cataract Extraction History in Older Adults? An Analysis from the US Population - Osama M. Mustafa; Yassine J. Daoud (Journal of Ophthalmology, 2020)
Background. Galactose accumulation in the lens tissue is known to be cataractogenic. Whether consistent dietary intake of lactose—which consists of glucose and galactose—predisposes to senile cataract remains unclear. This study was conducted to investigate the association between a number of dietary milk intake indicators and cataract extraction history in a representative sample of older adults from the US population. Methods and Materials. This is a cross-sectional, population-based study. Participants of the United States National Health and Nutrition Examination Survey 2001–2008 who were ≥50 years old and provided a complete history of their usual daily dietary intake were included. Exclusion criteria were special diets, extreme daily energy intake, and missing outcome (i.e., cataract extraction history). Indicators of milk intake used were early-life intake regularity, current daily milk/total dairy intake amounts, and estimated lifelong milk exposure. Odds ratios (OR) and 99% confidence intervals (99% CI) were calculated with fitting weights to better represent the population-based estimates. Results. Among the 5930 studied participants, early-life milk intake regularity was not associated with cataract extraction history in age/sex/ethnicity-adjusted and multivariable-adjusted models (p trend = 0.064 and 0.094, respectively). Current daily milk intake was associated with a slight reduction in the likelihood of cataract extraction in the age/sex/ethnicity-adjusted model (OR = 0.885 per cup equivalents, 99% CI = 0.795–0.986) and in the multivariable model (OR = 0.871 per cup equivalents, 99% CI = 0.746–0.993). However, no such association was observed between quartiles of current dietary milk intake and cataract extraction history (p=0.154 and p=0.317 for age/sex/ethnicity-adjusted and multivariable-adjusted models, respectively). Neither current total dairy intake nor estimated lifelong milk exposure was significantly associated with the outcome in the final multivariable models. Conclusion. There appears to be no direct relationship between several indicators of dietary milk consumption and cataract extraction history in the general American population.